Surface Water Quality In peri-Urban Areas In Dar Es Salaam, Tanzania: The Case Of Ng’ombe River - Malale, M. P.; Munishi., Subira, (Tanzania Journal of Engineering and Technology, 2018)
This work made an ecological assessment of the Ng ' ombe River based on water chemistry. Ng ' ombe River traverses the unplanned and densely populated areas in Dar es Salaam forms and discharges into the Msimbazi River. This particular study sought to identify the pollution levels and their sources. River water-sampling locations were chosen and samples of water were taken from the river and analyzed according to standard analytical procedures. The water quality parameters that were studied include temperature, pH, total suspended solids (TSS), electrical conductivity (EC), turbidity, biochemical oxygen demand (BOD5), phosphate (PO4 3-), total phosphorus (TP), nitrate-nitrogen (NO3-N) and faecal coliform. Interviews were carried out with at least 100 residents to measure their awareness, perception on the river pollution and the importance they place on conserving the River. The study gave an indication of organic and faecal pollution on Ng ' ombe River. Bacteriological quality of the River was found to be low, with BOD5 and faecal coliform levels exceeding the permissible limits. The BOD5 ranged from 80 to 190 mg/l and the faecal coliform concentration was between 1200 to 5200 cfu/100ml. The physical water quality was consistently low during rainfall periods, with some parameters exceeding Tanzania Bureau of Standards (TBS) or World Health Organization (WHO) permissible limits. Some of the monitored physico-chemical parameters of river includes; Electrical conductivity (EC) which ranged from 1725 to 2950 ïS/cm; Total suspended solids (TSS) ranged from 80 to 180 mg/l and turbidity from 33 to 200 NTU. Further, the nutrient concentrations were NO3-N, which ranged from 0.80 to 1.71 mg/l, PO4 3- from 0.26 to 0.54mg/l and total phosphorus (TP) from 0.10 to 0.24 mg/l. Generally, water from stations located in unplanned or informal settlements had higher levels of pollutants compared to those from planned or formal settlements. It was also noted that the river pollution increased from upstream to downstream end. There was a clear impact of runoff manifested by the elevation of nutrient concentrations during rainy season. The results show degradation of the water quality of the river by anthropogenic activities in the area with poor solid management and low level of sanitation being significant causes of the pollution. Keywords: Informal settlement, Ng'ombe river, Urban rivers, Water Quality